Challenges Faced by People Living with HIV/AIDS in Cape Town, South Africa: Issues for Group Risk Reduction Interventions. (2nd August 2010) - Cloete, Allanise; Strebel, Anna; Simbayi, Leickness; van Wyk, Brian; Henda, Nomvo; Nqeketo, Ayanda
Abstract : This paper presents the findings of an exploratory study to investigate the challenges faced by people living with HIV/AIDS (PLWHA) in communities in Cape Town, South Africa. The primary goal of the study was to gather data to inform the adaptation of a group risk reduction intervention to the South African context. Qualitative methods were used to examine the experiences of PLWHA. Eight focus group discussions (FGDs) were conducted with 83 HIV-positive participants and 14 key informants (KIs) involved in work with PLWHA were interviewed. Findings revealed that AIDS-related stigma was still pervasive in local communities. This was associated with the difficulty of disclosure of their status for fear of rejection. Also notable was the role of risky behaviours such as lack of condom use and that PLWHA considered their HIV/AIDS status as secondary to daily life stressors like poverty, unemployment, and gender-based violence. These findings have implications for the adaptation or development of behavioural risk reduction interventions for PLWHA.